Pengembangan Perangkat Pembelajaran Matematika dengan Model Project Based Learning Terintegrasi Science Technology Engineering And Mathematics (STEM) dalam Meningkatkan Kemampuan Penalaran Matematis Peserta Didik Kelas VII SMP - Nidya Oktadila; Yerizon Yerizon; Edwin Musdi; Ali Asmar (JEMS: Jurnal Edukasi Matematika dan Sains, 2022)
Learning tools are one of the important things in the learning process that have an impact on students' abilities, especially mathematical reasoning abilities. Learning tools in the form of lesson plans and LKPD can create an effective and fun learning process, and can facilitate students' mathematical reasoning abilities. This research was conducted with the aim of developing learning tools that have valid, practical and effective characteristics on the mathematical reasoning abilities of seventh grade junior high school students. This type of research is development research using the Plomp model, which consists of three stages, namely the preliminary stage, the prototype-making stage and the assessment stage. The learning tools developed are lesson plans and LKPD with the PjBL – STEM model in improving students' mathematical reasoning abilities for class VII. The instruments used are validation sheets, observation sheets, questionnaires, interviews and tests. The results showed that: (1) Learning tools in the form of RPP and LKPD with the PjBL - STEM Model in improving students' Mathematical Reasoning Ability. already valid in terms of content and construct. (2) Practical because it is easy to use and understand, the allocated time is very efficient, interesting and contributes to learning. (3) From the results of the mathematical reasoning ability test, it shows that the PjBL – STEM learning tool in improving students' Mathematical Reasoning Ability has been effective in improving mathematical reasoning abilities seen from the results of the final test conducted on students.